SISTEM ELEKTRONIK DATA INTERCHANGE DALAM KOMUNIKASI AWAK KAPAL TUGBOAT PATRA TUNDA 3001 - DEDENG WAHYU EDI; ROHMAT ARIYONO (Institut Transportasi dan Logistik Trisakti, 2015)
Technology developments, particularly in the services sectors, continue to grow along with the advancing of time. The implementation of electronic data interchange system at PT Pertamina Trans Continental is so helpful for Tugboat crew Patra Tunda 3001 to communicate. Using qualitative descriptive methods and data analysis techniques with simple linear regression analysis, correlation coefficient analysis, determinant coefficient analysis and hypothesis testing, it turns out that a linear regression line equation showed Y = 24.851 + 0.421 X. It means that there is an increase of one unit from each variable in the use of the system